Comparison of Estimation of Glomerulus Filtration with MDRD and CKD-EPI Formula in Diabetes Mellitus Patients Type 2 in Bhayangkara Hospital Palembang - Abdul Mutholib; Asrori; Refai; Wahyu Dwi Ari Wibowo (East Asian Journal of Multidisciplinary Research, 2023)
Patients with uncontrolled type 2 diabetes mellitus (DM) can be at risk of complications with the kidneys. The decrease in the condition of the kidneys impacts the ability of the glomerulus to filter. This study aims to compare the estimated glomerular filtration rate (eGFR) based on Creatinine Levels with MDRD and CKD-EPI Formulas. The research was conducted with a cross-sectional approach. The study was carried out from March to April 2021. The sample size of this study was 97 data points on Type 2 DM. The result shows the average eGFR values with the MDRD and CKD-EPI formulas in people with Type 2 DM were 97.85 ml/min/1.73 m2 and 85.67 ml/min/1.73 m2. From the Mann-Whitney test, the results obtained were p> α (0.05), p-value = 0.3498. There were differences in the eGFR values calculated by the MDRD and CKD-EPI formulas.